USAGE OF SCRATCH IN MAKING GAME-BASED MATHEMATICS LEARNING MEDIA TO IMPROVE STUDENTS' MATHEMATICAL SKILLS - Barra P. Pradja; NISVU NANDA SAPUTRA (Prima: Jurnal Pendidikan Matematika, 2023)
This research is to see the use of Scrath as a media creation tool for Game-based mathematics learning to improve mathematical abilities, the improvement of mathematical abilities assessed is problem-solving and mathematical reasoning. This type of research is development research using the ADDIIE model (Analysis, Design, Development, Implementation, Evaluation) the research subject is grade VIII junior high school students and the research location is at SMP Dharma Siswa Kota Tangerang with 33 research subjects. Game-based Learning Media before being implemented was validated by experts, the validation results stated that the media was in the valid category and could be used in schools. After being implemented in schools, it is known that game-based learning media can improve mathematical reasoning skills and mathematical problem-solving skills are at a good level